Удосконалення маркетингових конкурентних стратегій аграрного підприємства - Багорка, Марія Олександрівна; Bahorka, Mariia; Абрамович, Інна Ананіївна; Abramovych, Inna (Університет економіки і підприємництва, 2024)
В статті розглянуто основні проблеми сучасного функціонування аграрних підприємств, визначена роль маркетингових конкурентних стратегій, представлені базові конкурентні стратегії та алгоритм їх розробки, сформовані дієві пропозиції їх удосконалення. На підставі теоретичних обґрунтувань встановлено, що конкурентоспроможність підприємства – це рівень його потенціалу, який забезпечує здатність утримувати або розширити свою частку ринку в конкурентному середовищі. Існує багато стратегій досягнення конкурентоспроможності переваги, але базовими конкурентними стратегіями є: стратегія зниження собівартості продукту, продуктова стратегія диференціації, стратегія сегментації, інновація стратегія, стратегія негайного реагування на потреби ринку. Розробка маркетингової конкурентної стратегії є одним із важливі складові підвищення конкурентоспроможності підприємств аграрної галузі і передбачає вибір, виявлення адаптивних особливостей при розробці та оцінюванні альтернативних конкурентних стратегій. Розробка сучасної комплексної конкурентної стратегії підприємства повинна поєднувати і гармонізувати цілі та завдання стратегій різних рівнів. The article examines the main problems of the modern functioning of agricultural enterprises, defines the role of competitive marketing strategies, presents basic competitive strategies and their development algorithm, and formulates effective proposals for their improvement. The marketing strategy of the enterprise allows you to understand how to plan everything and implement the types of activities at the enterprise aimed at fulfilling plans and tasks. At the same time, the marketing strategy is one of the parts of the general strategic plan of the agricultural company. Marketing strategy is related to issues aimed at increasing sales and income of the enterprise. It should be developed by experienced specialists, based on the resource potential of the enterprise and the possibilities of its use over a long period of time. On the basis of theoretical justifications, it was established that the competitiveness of an enterprise is the level of its potential, which ensures the ability to maintain or expand its market share in a competitive environment. There are many strategies for achieving competitive advantage, but the basic competitive strategies are: the strategy of reducing the cost of the product, the product differentiation strategy to create a competitive advantage, the segmentation strategy, the innovation strategy, the strategy of immediate response to market needs. The development of a competitive marketing strategy is one of the important components of increasing the competitiveness of agricultural enterprises and involves the selection and identification of adaptive features in the development and evaluation of alternative competitive strategies. The development of a modern comprehensive competitive strategy of an enterprise should combine and harmonize the goals and objectives of strategies at different levels. We offer the implementation of a strategy of immediate response to the needs of the market, aimed at meeting the needs arising in agribusiness as quickly as possible. The main principle of behavior is the selection and implementation of the most profitable projects in the current market conditions. Enterprises aimed at rapid response are ready for immediate reorientation of production, changing its scale in order to obtain maximum profit in a short period, despite the unit costs determined by the absence of any specialization of its production
Improvement of marketing competitive strategies of agricultural enterprises
Keywords: маркетингова стратегія; marketing strategy; конкурентоспроможність; competitiveness; конкурентні переваги; competitive advantages; конкурентні стратегії; competitive strategies; споживачі; consumers; конкуренти; competitors; диференціація; differentiation; адаптація; adaptation